Coherence [videorecording (DVD)] - Byrkit, James Ward; Manugian, Alex; Foxler, Emily, 1984-; Armstrong, Hugo; Gracen, Elizabeth, 1961-; Maher, Lauren; Brendon, Nicholas, 1971-; Scafaria, Lorene; Sterling, Maury, 1971-; Sadler, Nic, 1965-; Muller, Arlene; Dyrud, Kristen Øhrn (Oscilloscope Laboratories, 2015)
On the night of an astronomical anomaly, eight friends at a dinner party experience a troubling chain of reality bending events. Part cerebral sci-fi and part relationship drama, a tightly focused, intimately shot film that quickly ratchets up with tension and mystery.